The Influence of Accounting Understanding, Self Efficacy on the Digitalization of MSMEs, and the Quality of Financial Reports on MSMEs in Bantul Regency, Yogyakarta - Budiantara, Martinus; Sundjoto, Sundjoto; Zailani, Ludfi; Kurniawan, Moh Adi (Universitas Alma Ata, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in the Indonesian economy, with a large contribution to Gross Domestic Product (GDP) and employment absorption. However, many MSMEs face challenges in preparing quality financial reports, especially related to accounting understanding, self-efficacy, and digitalization. This study aims to analyze the effect of accounting understanding, self-efficacy, and digitalization on the quality of MSME financial reports, with digitalization as a mediating variable. Through a quantitative approach, this study involved 50 MSMEs in Bantul, Yogyakarta, and used analysis with SmartPLS. The results of the study indicate that MSME digitalization and accounting understanding have a significant effect on the quality of financial reports, while self-efficacy has no direct effect. Digitalization acts as a mediator between accounting understanding and financial report quality. This study contributes to the literature on MSME financial management as well as practical recommendations for MSME actors in improving the quality of financial reports through the use of digital technology.